Orai1 is an Entotic Ca2+ Channel for Non‐Apoptotic Cell Death, Entosis in Cancer Development - Ah Reum Lee; Chan Young Park (Advanced Science, 2023)
Abstract Entosis is a non‐apoptotic cell death process that forms characteristic cell‐in‐cell structures in cancers, killing invading cells. Intracellular Ca2+ dynamics are essential for cellular processes, including actomyosin contractility, migration, and autophagy. However, the significance of Ca2+ and Ca2+ channels participating in entosis is unclear. Here, it is shown that intracellular Ca2+ signaling regulates entosis via SEPTIN‐Orai1‐Ca2+/CaM‐MLCK‐actomyosin axis. Intracellular Ca2+ oscillations in entotic cells show spatiotemporal variations during engulfment, mediated by Orai1 Ca2+ channels in plasma membranes. SEPTIN controlled polarized distribution of Orai1 for local MLCK activation, resulting in MLC phosphorylation and actomyosin contraction, leads to internalization of invasive cells. Ca2+ chelators and SEPTIN, Orai1, and MLCK inhibitors suppress entosis. This study identifies potential targets for treating entosis‐associated tumors, showing that Orai1 is an entotic Ca2+ channel that provides essential Ca2+ signaling and sheds light on the molecular mechanism underlying entosis that involves SEPTIN filaments, Orai1, and MLCK.